Traumatic isolated perforation of lower oesophagus. (October 2016) - Mzoughi, Z.; Djebbi, A.; Bayar, R.; Hamdi, I.; Gharbi, L.; Khalfallah, T.
Abstract: One of the rarest cases of non-iatrogenic oesophageal perforation is falling from height. We report a case of a 26 year old man with oesophageal perforation resulting from a fall of 12 meter height. A pneumomediastinum in the absence of a pneumothorax and contrast extravasation from the oesophagus on CT evoked a perforation of the aerodigestive tract. No other injuries were seen. A non-operative management was pursued with good outcomes.